2002
DOI: 10.1520/gtj11087j
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Surface Area of Fine-Grained Soils by the Ethylene Glycol Monoethyl Ether (EGME) Method

Abstract: This paper describes a test procedure for determining the total surface area of fine-grained soils using the Ethylene Glycol Monoethyl Ether (EGME). The test involves saturating a soil sample with EGME and then removing the excess EGME in a vacuum desiccator, until the EGME forms a monomolecular layer on the soil surface. The results of the test are expressed as Specific Surface Area (SSA), which describes the surface area/unit mass of dry soil with units of m2/g. Test results are presented demonstrating the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…The grain size distribution of the materials is measured by a Mastersizer 2000. The total surface area is determined by the ethylene glycol monoethyl ether (EGME) method suggested by Cerato and Luteneggerl (2002). The dominant minerals of the kaolin and bentonite are kaolinite and montmorillonite, respectively, based on the X-ray diffraction analysis.…”
Section: Soil Bentonite and Zeolitementioning
confidence: 99%
“…The grain size distribution of the materials is measured by a Mastersizer 2000. The total surface area is determined by the ethylene glycol monoethyl ether (EGME) method suggested by Cerato and Luteneggerl (2002). The dominant minerals of the kaolin and bentonite are kaolinite and montmorillonite, respectively, based on the X-ray diffraction analysis.…”
Section: Soil Bentonite and Zeolitementioning
confidence: 99%
“…These underwent additional mineralogical analysis to investigate the physicochemical mechanisms giving rise to the dielectric response. The SSA was determined using sorption of 2-ethoxyethanol (EGME) (Kellomäki et al, 1987;Cerato and Lutenegger, 2002) (see Appendix A), which is chosen because of its suitability for investigating interlayer surfaces in swelling clays ( Table 1). The CEC was determined using methylene blue (MB) and the tetrasodium pyrophosphate method of Wang et al (1996) (see Appendix A).…”
Section: Mineralogy Cation Exchange Capacity and Specific Surface Areamentioning
confidence: 99%
“…The SSA was determined using sorption of EGME (Kellomäki et al, 1987;Cerato and Lutenegger, 2002), which is chosen because of its suitability for investigating interlayer surfaces in swelling clays. A sample of 1-2 g of powder is dried at 110°C to drive off as much water as possible.…”
Section: Specific Surface Areamentioning
confidence: 99%
“…The ethylene glycol monoethyl ether (EGME) method has been used to calculate both the external and internal specific surface area of the soils (interlayer surfaces of soils and clays) [26,105,106]. In different studies done using kaolinite from different locations it was found that the specific surface area of kaolinite was 25.5 m 2 ·g −1 [107], 5.9 m 2 ·g −1 [108] and 15 m 2 ·g −1 [106]. It has been stated in the literature that non-expanding soils like kaolinite have SSA values ranging from 10 m 2 ·g −1 to 40 m 2 ·g −1 [106].…”
Section: Kaolinitementioning
confidence: 99%
“…In different studies done using kaolinite from different locations it was found that the specific surface area of kaolinite was 25.5 m 2 ·g −1 [107], 5.9 m 2 ·g −1 [108] and 15 m 2 ·g −1 [106]. It has been stated in the literature that non-expanding soils like kaolinite have SSA values ranging from 10 m 2 ·g −1 to 40 m 2 ·g −1 [106]. …”
Section: Kaolinitementioning
confidence: 99%